Complete chloroplast genome of Zingiber mioga by de novo sequencing. Issue 3 (4th March 2021) - Jiang, Ping; Huang, Renshu; Sun, Taotao; Chen, Cunwu; Zuo, Ruihua; Taoa, Ying
Abstract: Zingiber mioga (Thunb.) Rosc. ( Zingiber mioga ) is an important edible species, which also has important medical and natural pigment value. This article is firstly reported the Zingiber mioga's chloroplast genomes which detect by de novo sequencing. The results showed that the length sequence of Zingiber mioga's chloroplast genome was 163, 541 bp, and the length of LSC, SSC, and two IR regions was 88, 035, 15, 886, and 29, 810 bp, respectively. Zingiber mioga's chloroplast genome was encoded 135 genes involving 10 rRNA, 38 tRNA, and 87 protein-coding genes. After phylogenetic and cluster analysis, the Zingiber were closest approach to Zingiber mioga, followed by Kaempferia, Curcuma, Hedychium, and Roscoea .